Spontaneous Obliteration of a Dissecting Aneurysm of Recurrent Artery of Heubner Monitored by Serial Magnetic Resonance Vessel Wall Imaging - Nakazaki, Asuka; Ito, Masaki; Isobe, Masanori; Takahashi, Takeshi; Nomura, Taichi; Fujihara, Fumiaki; Isu, Toyohiko; Sugiyama, Taku; Osanai, Toshiya; Fujimura, Miki (Asian Journal of Neurosurgery, 2022)
Aneurysms of the recurrent artery of Heubner (RAH) are known to be one of the uncommon cerebral aneurysms, predominantly presenting with bleeding symptoms. Previously, nine cases of the RAH aneurysms have been reported, all of which were treated surgically or endovascularly and most cases developed postoperative cerebral infarct in the ipsilateral caudate nucleus. Herein, we report a man presenting with transient ischemic attack due to diffuse cerebral vasospasm from a minor non-disabling subarachnoid hemorrhage (SAH) from an RAH aneurysm. He visited our hospital 7 days after the first experience of a thunderclap headache complaining with transient unilateral motor weakness and thin SAH in the right sylvian fissure. Diagnostic catheter angiography revealed a dissecting fusiform aneurysm (8 mm in size) originating from the left RAH contralateral to the thin SAH. Contrast-enhanced magnetic resonance vessel wall imaging (MR-VWI) helped to identify the ruptured nature of the RAH aneurysm. Owing to his delayed ischemic condition after minor SAH, he was conservatively treated with serial MR-VWI monitoring. The aneurysm was spontaneously obliterated with an asymptomatic lacunar infarct in the ipsilateral caudate nucleus in a month. Together, this case was considered as the dissecting aneurysm of RAH with a favorable outcome after the conservative management. Although long-term follow-up is mandatory because the disappearance of the vessel wall enhancement does not necessarily secure the permanent cure of the lesion, serial MR-VWI is helpful to diagnose the ruptured nature and monitor its chronological change in combination with conventional radiological imaging techniques.
Keywords: MRI; recurrent artery of Heubner; vascular disorder; vessel wall imaging